Structum (chondroitin sulfate) in treatment of osteoarthritis - O J Varga; V K Ignatjev; N N Vesikova; I M Marusenko (Научно-практическая ревматология, 2003)
Objective. To assess Structum (chondroitin sulfate) efficacy in treatment of osteoarthritis in Republic of Karelia. Methods. 34 pts with osteoarthritis (mean disease duration 6,44±0,67 years) were included. Functional Leken score (FLS), pain at rest and at walk on visual analog scale (VAS), pts nonsteroidal anti-inflammatory drugs (NSAID) requirement (diclofenac daily requirement in mg), percent of pts refused NSAID treatment, achievement of clinically significant improvement (40% decrease of FLS and/or 50% decrease of NSAID requirement) were regarded as variables for the evaluation of therapy efficacy. Results. Structum administration in pts with osteoarthritis provided reduction of FLS, pain at rest and at walk, NSAID requirement and in some cases allowed to withdraw of NSAID completely. Structum has good safety and is effective in doctor and pts opinion. Conclusion. Structum is an effective drug for treatment of osteoarthritis.